A general fabrication approach on spinel MCo2O4 (M = Co, Mn, Fe, Mg and Zn) submicron prisms as advanced positive materials for supercapacitor. (1st February 2018) - Gao, Hongyan; Li, Yafei; Zhao, Haihong; Xiang, Junjie; Cao, Yan
Abstract: The design and fabrication of advanced electrode materials for supercapacitor have been extensively explored recently. The spinel transition metal oxides have drawn considerable attentions because of their high theoretical capacity to store electrical charge. This work introduced a general hydrothermal assisted co-precipitation approach to fabricate five kinds of spinel MCo2 O4 (M = Co, Mn, Fe, Mg and Zn) submicron prisms on nickel foams. Among these spinel MCo2 O4 electrodes, the MgCo2 O4 exhibited the highest specific capacity of 613.5 C g −1 (0.883 C cm −2 ) at a current density of 2 mA cm −2 . All the specific capacities of bimetallic oxides were higher than single metal oxide Co3 O4, indicating the enhanced electrochemical performance of bimetallic oxides. The correlations between peak currents and the square root of the scan rates of all prepared electrode materials showed OH − diffusion-controlled characteristic in their redox reactions. Furthermore, an assembled MgCo2 O4 //AC hybrid supercapacitor (HSC) achieved a specific capacity and a specific energy of 182.8 C g −1 at 0.5 A g −1 and 39.7 W h kg −1, respectively. More impressively, this MgCo2 O4 //AC HSC showed a subsequent increase about 21.1% in specific capacity after 5000 cycles, suggesting its promising characteristics for the next generation energy storage device. Graphical abstract: Image 1 Highlights: A general route for the synthesis of MCo2 O4 (M= Co, Mn, Fe, Mg and Zn) submicron prisms was developed. MCo2 O4 submicron prisms exhibited the OH - diffusion-controlled characteristic of the redox reactions. MgCo2 O4 submicron prisms achieved a highest specific capacity of 613.5 C g -1 at 2 mA cm -2 . Excellent cyclability with 121.1% retention after 5000 cycles was achieved by MgCo2 O4 //AC supercapacitor.